Frequency of Musculoskeletal Impairments or Disorders among Covid-19 patients recovered six months back - Rabia Jawa, Muhammad Ammar Akbar, Sania Maqbool, Tamknat Ilyas, Sameen Arshad, Ali Hayder, Ossama Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: COVID-19 is essentially an illness brought about by corona virus. COVID-19 is transmitted primarily by close contact between infected individuals. COVID-19 has been related to myalgia and general weakness in one-quarter to one- portion of suggestive patients. Aim: To recognize the number of Covid-19 recovered patients who at present complain of musculoskeletal impairments. Methods: This was an observational study in which 181 covid-19 recovered patients were surveyed. Data was collected from different hospitals of Pakistan, through self-made questionnaire and analyzed by SPSS version 21. Results: After the collection of data, gender differences exist in musculoskeletal disorders after comparison of both genders with age group 20 to 50 years with 48% are males 58% are females and pie chart shows prevalence of musculoskeletal disorders among covid-19 recovered patients. According to the findings, around 35% of 181 healed patients (with pain in their body parts) have seen a doctor in the last 6 months, while 65% have not visited a hospital to consult a doctor for MSK disease Practical Implication: Musculoskeletal impairments are leading cause of pain and disability that can lead to deformity if remain untreated or left without prior notice. As Covid-19 infection rate is getting higher day by day and till date vaccination is not available to everyone here. We must ensure that anyone getting infected by the novel Corona can have least negative effects even after patients get cured. Conclusion: Gender differences exist in musculoskeletal problems. We have to compare it with Covid. Here we may say that it may be due to more stress among females, there are more chances of MSK issue among females as compared to males Keywords: Covid-19, musculoskeletal impairments, restriction of activities